Cleaning Removable Orthodontic Appliances - Maha Isam Abdalaziz (Dentistry 3000)
Objective: Removable appliances are fabricated by different types of material like auto polymerizing acrylic resin, heat polymerizing acrylic resin, and light polymerizing acrylic resins. These materials have some built in characteristic that make them prone to bacterial aggregation and biofilm formation. Denture hygiene methods have been suggested to keep these appliances clean during the time of treatment, like toothbrushes, toothpaste, commercial mouthwash, denture cleansers and others. The primary aim of cleaning removable orthodontic appliances is to maintain oral hygiene, prevent plaque buildup, and protect the health of both the appliance and the teeth. Material and Methods: 45 samples were taken from different people wearing removable orthodontic appliances. Swabs were taken from the appliances before and after using the disinfectant for two weeks to determine its effect on the microorganisms present in the orthodontic appliance. This was done by passing these swabs in bacterial culture media and performing a bacterial count of the sample before and after the disinfection process. On this basis, a comparison was made, and the effect of the disinfectant materials was determined. Results: Mouthwash was the most effective agent against all types of bacteria, especially Klebsiella pneumonia and Escherichia Coli. Normal saline was the least effective, with minimal reduction rates against all types of bacteria. Water and salt (tap water) was moderately effective, with reasonable reduction rates against most types of bacteria. Conclusion: Mouthwash was the most effective disinfectant for cleaning removable orthodontic appliances, significantly reducing bacterial growth. Salted tap water offers moderate efficacy, while normal saline is the least effective.